Comparing the effects of static and dynamic signals during multiple schedules. (2nd November 2022) - Campos, Claudia; Bloom, Sarah E.; Kollin, Lori; Weyman, Jennifer R.
Abstract: The extent to which multiple schedules are an effective schedule thinning method following functional communication training (FCT) relies on the control the schedule‐correlated stimuli exert over behavior. Thus, the stimuli used to signal the schedule in place (e.g., reinforcement and extinction) in a multiple schedule arrangement require special attention. To date, the majority of the research on multiple schedules has evaluated the use of different arbitrary signals as schedule‐correlated stimuli (e.g., poster boards). These signals are considered static as they lack movement. More recently, some studies have successfully used dynamic signals, which include movement or animation, within multiple schedule arrangements. However, the extent to which one type of signal may result in faster stimulus control over behavior has not been evaluated. Thus, the purpose of this study was to compare the use of static and dynamic signals as schedule‐correlated stimuli in multiple schedules used within the context of FCT. Four children diagnosed with autism spectrum disorder participated in the study. The results suggest that no differences in discriminated manding were observed for three out of four participants. Only dynamic signals resulted in discriminated manding for one participant.